The contribution of Agriculture Sector in the Economy of Afghanistan (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this study is to identify the contribution of agriculture to the Afghanistan economy by examining the experience of 34 provinces as documented in commissioned case studies and various secondary sources (CSO directory, FAO reports, government publications, USAID reports, NGO reports, journals, and websites) for the period 2016 - 2017. Agriculture is the backbone of the Afghan economy, the contributions of agriculture to the country’s gross demotic product (GDP) is 23% in 2017, while the labor force engaged in this sector is around 61.6%. The annual growth rate in Afghanistan is predictable 3.6%. Afghanistan produces organic fruits, nuts, grain, vegetables and livestock products including cashmere, skin, wool, and a significant amount of these commodities is moving towards the export market. Agriculture represents about one-quarter of national GDP and is the second largest sector after services. Over the 70 % of the population are poor living in rural areas, and agriculture plays a significant role in their livelihoods. The most Afghan farms are very small, and their productivity is low over the years that farmers produce to satisfy the food needs of their household, with limited agricultural production entering commercial marketing channels and the trade account deficit overall. The GDP including opium was US 20.3 billion with GDP per capita of US 697. The agricultural sector is entirely run by private enterprises, including farmers, cooperatives, input suppliers, herders, agribusiness processors, and exporters.